Response to “What Constitutes a Just Match?: A Reply to Murphy” by D. Micah Hester (CQ Vol 12, No 1): Of Need, Justice, and Random Acts of Education - Murphy, Timothy F. (Cambridge quarterly of healthcare ethics, 2004)
D. Micah Hester thinks the residency match system helps sustain the divide between the haves and the have-nots in healthcare. He believes that the match system channels talent away from the have-nots in a more or less systematic way, damaging moral values in physicians as it goes. As a way of making inroads against these effects, he has asked whether assigning medical school graduates to residencies at random would distribute talent and educational opportunity more broadly and promote desirable moral values. I pointed out what I think are serious limitations of this proposal, and Hester has extended me the courtesy of a reply. Yet with that reply, I find that he has made it even more difficult to defend a lottery approach to residency assignment.